An experimental data-set on merging flows in rail tunnel evacuation. (November 2017) - Cuesta, Arturo; Abreu, Orlando; Balboa, Adriana; Alvear, Daniel
Highlights: Merging flows during evacuation in rail tunnels are investigated. A full-scale mockup of a train exit and a lateral walkway is used. We found that the higher the rail car exit the more dominance of the walkway flow. Nothing suggests gender role linked to deference behaviours. Abstract: The main purpose of this study was to investigate the impact of merging conditions during evacuation process in rail tunnels. The experiment was carried out in a mock-up of a rail car with a single exit towards a lateral corridor. Eight exit configurations were tested involving 77 participants with a reasonable proportion of ageing subjects (age mean 48; standard deviation 15; range 18–74). New measurements and data processing methods were proposed and used. The novel contribution of this study was the use of flow distributions rather than flow rates. The proposed new random variable (the instantaneous specific flow) is derived from a straightforward way of measuring the flows (i.e. the time intervals between participants passing a reference line). The collected flows were classified and combined to produce a set of 10 flow samples for the statistical analysis. Observations from video recordings complemented the quantitative analysis revealing behavioural patterns of participants. The results confirmed that the occurrence of merging had a negative effect during evacuation. The rail car exit flow and the walkway flow decreased when merging occurs. The relationship between both flows varied considerably during the merging period. However, the higher the height differential of the rail car exit the more dominance of the walkway flow. It is also found no gender playing a role in deference behaviour (male helping female).